Evaluasi Indeks Konsumsi Energi Listrik di Rumah Sakit Daerah Umum R.A. Kartini Jepara - Kurniawan, Samuel; Safrizal, Safrizal; Arifin, Zaenal (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2025)
This study aims to evaluate the electrical energy consumption index at the R.A. Kartini Regional General Hospital (RSUD Jepara). Electrical energy efficiency is a crucial aspect in the management of modern health facilities, especially in efforts to reduce operational costs and environmental impacts. Hospitals as facilities that operate 24 hours have high energy consumption, especially for medical equipment, air conditioning systems, and lighting. This study uses a quantitative descriptive analysis method by processing electricity consumption data in 2018 obtained from official hospital documents. The results showed that the total installed power at the R.A. Kartini Regional General Hospital Jepara reached 1,410,005 VA, with the largest distribution of energy use in medical devices (51.5%), air conditioning systems (38.7%), and mechanical equipment (20.7%) The hospital's Energy Consumption Index (IKE) was calculated at 146 kWh/m²/year, which is included in the